2018
DOI: 10.1108/ccsm-06-2017-0078
|View full text |Cite
|
Sign up to set email alerts
|

Confucianism: measurement and association with workforce performance

Abstract: PurposeThis paper reconsiders the approaches to measuring Confucian values, and tests their association with workforce performance. The purpose of this paper is to examine how such values and performances are prioritized across three East Asian societies, but more importantly, identifies how variations across societies might result from the way in which Confucianism has been transformed/appropriated differently across history.Design/methodology/approachA Best-Worst experimental design is used to measure three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 109 publications
(137 reference statements)
3
47
0
Order By: Relevance
“…This suggests that there might be differences in the effect of Confucian values on public entrepreneurship and organisational performance among countries because of their unique contextual circumstances. This result is in line with the recent findings of Viengkham, Baumann, and Winzar's (2018) work on Confucianism and workforce performance, which assumed varied prioritizations of Confucian values among people in different societies (China, Taiwan, and South Korea) and found variations in their impact on workforce performance among them.…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that there might be differences in the effect of Confucian values on public entrepreneurship and organisational performance among countries because of their unique contextual circumstances. This result is in line with the recent findings of Viengkham, Baumann, and Winzar's (2018) work on Confucianism and workforce performance, which assumed varied prioritizations of Confucian values among people in different societies (China, Taiwan, and South Korea) and found variations in their impact on workforce performance among them.…”
Section: Discussionsupporting
confidence: 90%
“…As argued by Leong, Huang, and Mak (), a work ethic construct can offer important variables to consider “when providing career assessment and counseling services” (Leong et al, , p. 313). Also, similar to what was argued by Viengkham et al (), the findings of this research can help develop initiatives to prepare individuals for fulfilling their assignments by providing contextual knowledge on the individuals' attitudes toward work in the Chinese context.…”
Section: Implications For Human Resource Developmentsupporting
confidence: 81%
“…Moreover, performance as one of the concerns of HRD, is highly related to work ethic of employees (Meriac & Gorman, ; Viengkham, Baumann, & Winzar, ; Wang, Wang, Ruona, & Rojewski, ). We argue that examining the work ethic and influence of its cultural and organizational antecedents could have important implications for HRD initiatives (Petty & Hill, ; Viengkham et al, ). Specifically, current study has practical implications for HRD professionals who want to customize their practices in Asia.…”
Section: Implications For Human Resource Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Confucianism serves as East Asian society’s core value system and ethical foundation for business and social interactions, thereby affecting people’s thinking styles and behaviors in business contexts (Kim, 2009). Many believe that Confucian values, such as the emphasis on education, hard work, frugality, and the importance of knowledge have contributed to economic success in East Asian countries (Baumann et al, 2016; Viengkham et al, 2018). The cross-cultural management literature has explored the connection between the components of Confucianism and workforce performance and found that in a Korean context, Confucian values—hierarchy, competition, and value of knowledge—contribute to an employees’ motivation to succeed (Viengkham et al, 2018).…”
mentioning
confidence: 99%